2020
DOI: 10.1177/2055116920916956
|View full text |Cite
|
Sign up to set email alerts
|

Rectal duplication in an adult cat: a novel transanal surgical approach

Abstract: Case summary A 3-year and 8-month-old male entire European domestic shorthair cat was presented with a history of recurrent rectal prolapse, straining and pain when defaecating. Previous non-surgical and surgical treatments had not provided a satisfactory result. Rectal prolapse had recurred within 2 weeks of treatment. Upon clinical examination, an intraluminal mass could be palpated rectally. A CT scan examination revealed the mass was of a cystic nature and the cyst was surgically excised via a transanal ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
(130 reference statements)
1
6
0
Order By: Relevance
“…Most studies have described duplications in cats as cystic with an independent lumen (93%, n= 13/14) (Radlinsky et al, 2005;Kershaw et al, 2008;Parry-Smith et al, 2008;Kook et al, 2010;Bernardé et al, 2014;Doran et al, 2015;Hobbs et al, 2015;Agut et al, 2017;Kramer et al, 2017;Turner et al, 2019;Carbonell Buj et al, 2020), similarly to our case cyst's features. In humans most duplications are cystic with no lumen communication, whereas some are cylindrical structures that can or not have direct intestinal communication (Bhatt et al, 2020 Multiple level enteric duplications are rather uncommon but have been reported to occur in humans, with oesophageal duplication associated with small bowel duplication being the most frequent combination (Hur et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Most studies have described duplications in cats as cystic with an independent lumen (93%, n= 13/14) (Radlinsky et al, 2005;Kershaw et al, 2008;Parry-Smith et al, 2008;Kook et al, 2010;Bernardé et al, 2014;Doran et al, 2015;Hobbs et al, 2015;Agut et al, 2017;Kramer et al, 2017;Turner et al, 2019;Carbonell Buj et al, 2020), similarly to our case cyst's features. In humans most duplications are cystic with no lumen communication, whereas some are cylindrical structures that can or not have direct intestinal communication (Bhatt et al, 2020 Multiple level enteric duplications are rather uncommon but have been reported to occur in humans, with oesophageal duplication associated with small bowel duplication being the most frequent combination (Hur et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…In our case, the cyst fulfilled the three anatomic criteria defined by Gross and colleagues (1952) to be considered a duplication since it was (1) associated with the alimentary tract, (2) had a smooth muscle layer and (3) had gastrointestinal-like epithelium according to histopathology analysis. Only twelve other reports have been found in literature describing similar alimentary tract duplications in cats (Radlinsky et al, 2005;Kershaw et al, 2008;Parry-Smith et al, 2008;Kook et al, 2010;Bernardé et al, 2014;Doran et al, 2015;Hobbs et al, 2015;Agut et al, 2017;Kramer et al, 2017;Turner et al, 2019;Carbonell Buj et al, 2020;Fruehwald and Ellison 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations